Sava transformation chronicle (A) - Filipović, Nenad (Mednarodno inovativno poslovanje, 2023)
This case study is part of a sequel of cases (from A to D) prepared to be used together in a course on Strategic Management (more in particular on topics related to Mergers and Acquisitions, Business Portfolio Management and Corporate Transformation). Due to the article length restrictions, parts B –D, as well as the case Teaching Note, will be published in a separate article. Please refer to the Teaching Note for more precise suggestions related to classroom use.
Keywords: Sava (Kranj); strateški management; študija primera